Short-term effects of kinesiology taping on static and dynamic balance in healthy subjects - Zhou, Tianyu; He, Lin; Huang, Fasen; Sharp, Tim; Hou, Xiao (Frontiers in human neuroscience, 2024)
As a therapeutic tool, kinesiology taping (KT) has become increasingly popular for musculoskeletal injuries utilized by physiotherapists. KT has been found to have effects on facilitating muscle strength by generating a concentric pull on the fascia. However, little is known about KT in the improvement of dynamic and static balance. This study aims to explore whether KT on the quadriceps muscle has any immediate effects on static and dynamic balance. Twenty-seven healthy individuals (13 males and 14 females, aged 22 to 29) were recruited in a crossover study with two conditions: KT and no taping. KT was applied to the quadriceps muscle for the taping group, with the control receiving no taping. Pre- and post-test measurements were taken to give an indication of the effect of the tape on balance performance. Center of Pressure Excursion (COPE) and Time to Stabilization (TTS) when landing from a hop test and Y Balance test combined score (YBTCS) were used to assess a stabilizing balance activity and a dynamic balance. The pre- and post-intervention were collected, with differences explored using repeated measures ANOVA with time and condition (tape) factor analysis. We found a significant improvement ( ≤ 0.05) with a moderate to large effect size in YBTCS between KT and no taping, indicating enhanced balance performance in the KT group. However, no significant difference ( ≥ 0.05) with small to moderate effect size was found in COPE or TTS between the two conditions during landing tests, suggesting similar balance capabilities in these specific measures. The use of KT shows no significant immediate effect on static balance in healthy individuals when applied to the quadriceps muscles; however, it demonstrates a positive immediate effect on dynamic balance.